A criterion audit of women's awareness of blood transfusion in pregnancy - Leighton Nicola; Warren Peter; Rigby Claire; Khadra M; Johanson Richard (BMC, 2002)
Abstract Background In the Confidential Enquiry into Maternal Deaths (CEMD) Report, the very high risk of mortality in women who refuse blood transfusions is highlighted. The objectives were to establish current knowledge about, and views of transfusion in our pregnant population and to establish the level of compliance with the set audit standard. Method Questionnaire survey of 228 women, including both high and low risk pregnancies, attending ante-natal clinic between 2-9 May 2000 at the North Staffordshire Maternity Hospital, Stoke on Trent. Results The response rate was 100%. Only 43% were aware of the possible need for blood transfusion in pregnancy. If a blood transfusion was required, 92% stated that they would accept a blood transfusion in pregnancy. Four percent stated that they would not accept a transfusion because of religious reasons and risk of infection and the remaining four percent did not declare a reason. Conclusions This short survey identified that 57% of women were not aware of the possible need for blood transfusion during pregnancy. There is a need for more information to be shared on this subject with all antenatal women. Women who would refuse a transfusion need to be identified at booking and be referred for counselling and a management plan made for pregnancy, labour and delivery.